Concept and Proof of Principle of an Acoustofluidic Single-Particle Sorting Device Using a Spatially Confined Acoustic Active Region - Andreas Fuchsluger; Annalisa De Pastina; Tina Mitteramskogler; Rafael Ecker; Thomas Voglhuber-Brunnmaier; Nikolai Andrianov; Alexander Shatalov; Norbert Cselyuszka; Mohssen Moridi; Bernhard Jakoby (Proceedings)
We present the concept and a proof-of-principle experiment for an acoustofluidic single- particle sorter. In a microfluidic channel, a flow profile with the following three parallel fluid domains is generated: buffer fluid in the center and buffer plus particles in the lateral domains. Due to the laminar flow regime present in microfluidics, the particles essentially follow the stream line(s) along the channel. In the spatially confined sorting and detection region, by switching on the standing acoustic wave, particles of interest (POIs) are pushed into the center fluid domain, thus leaving the chip at the center outlet. For particles of non-interest (PONIs), the acoustic region remains silent, so PONIs are not centered and follow their path to the side outlet.